2017
DOI: 10.1007/s11814-017-0200-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of gold recovery from copper anode slime by acidic ionic liquid

Abstract: Hydrometallurgical gold recovery from primary or secondary sources is mainly based on a cyanide process, which is very dangerous for the environment due to the high toxicity levels. In view of the environmental effect, the present study proposes a new green solvent called 1-ethyl-3-methyl-imidazolium hydrogen sulfate (EmimHSO 4) ionic liquid (IL) to recover gold from copper anode slime (CAS). The optimum leaching conditions for maximizing gold recovery were determined by orthogonal array (OA) of Taguchi' s exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 54 publications
1
4
0
3
Order By: Relevance
“…3b, the gold recovery increased with increasing IL concentration, and reached quite high level with 97.32% recovery ratio at 80% (v/v) IL concentration after verification test. Considering the results of initial studies on gold recovery (Whitehead et al 2004, Rüşen andTopçu 2017a), the leaching yield obtained in this study seems to be quite compatible with the literature.…”
Section: Leaching Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…3b, the gold recovery increased with increasing IL concentration, and reached quite high level with 97.32% recovery ratio at 80% (v/v) IL concentration after verification test. Considering the results of initial studies on gold recovery (Whitehead et al 2004, Rüşen andTopçu 2017a), the leaching yield obtained in this study seems to be quite compatible with the literature.…”
Section: Leaching Resultssupporting
confidence: 90%
“…A small number of studies have been conducted by using ILs on the recovery of valuable metals from secondary sources such as electric arc furnace dust, brass waste and printed circuit boards, but most of these studies have been limited to recover Cu, Zn, and Pb from the secondary wastes (Bakkar 2014;Huang et al 2014;Kılıçarslan et al 2014). A recent study on recovery of precious metals from AS has been carried out by 1-ethyl-3-methyl-imidazolium hydrogen sulfate (EmimHSO 4 ) IL (Rüşen and Topçu 2017a), and results of this study showed that gold can be recover higher than 89% from AS at optimum leach conditions: 80% IL concentration, 75 °C, 4 h and 1/25 g/mL solid/liquid ratio. Also, authors mentioned that, other metals such as Pb, Sn, Se, Te (except for gold and copper) in anode slime have low dissolution rate in ILs.…”
Section: Introductionmentioning
confidence: 99%
“…Bakır anot çamurundan değerli metallerin geri kazanım süreçlerinin seçimi numunenin bakır içeriğine bağlı olmaktadır. Değerli metallerin bakır anot çamurlarından metalürjik yöntemlerle geri kazanımında genellikle asit liçi [6,7] oksidatif liç [8,9] mikrodalga ve ultrason destekli asit liçi [10,11], alkali füzyon yöntemi [12,13] ve yenilikçi bir yaklaşım olan iyonik sıvıların sulu çözeltileri [14,15] kullanılmıştır. Bu yöntemlerde fazla miktarda asit kullanılması, liç işlemlerinde geleneksel yöntemle ilave ekipman kullanılması ve bazı çözeltilerin maliyeti nedeniyle bakır anot çamurlarından metal geri kazanımı için ucuz, güvenli ve çevre ile uyumlu çözücü arayışı devam etmektedir.…”
Section: Introductionunclassified
“…BULGULAR VE TARTIŞMA3.1. Bakır anot çamurunun karakterizasyonuLiç deneylerinde kullanılan anot çamurunun kimyasal analizi ICP-MS ve kupelasyon yöntemi ile mineralojik yapısı ise önceki çalışmalarımızda belirtildiği üzere[14,15] XRD ve FE-SEM cihazları yardımıyla belirlenmiştir. Anot çamurun kimyasal kompozisyonu ve ihtiva ettiği mineralojik yapılar Çizelge 2'de gösterilmektedir.…”
unclassified
See 1 more Smart Citation